Metabolic and Endocrine Profile of Crossbred Pre-Ruminant calves under Extended Colostrum Feeding - Babitha V (Department of Physiology, College of Veterinary and Animal Sciences, 2003)
Colostrum is a highly fortified source of nutrients having seven times proteins, twice the total solids, higher content of vitamins, minerals and a very high immune value than normal milk. In most of the commercial dairy farms where day old weaning of calves is practiced, lion share of this potent calf protein supplement is practically wasted since colostrum is unmarketable for human consumption. In this circumstance, the present study was undertaken with the objective of evaluating the effects of enhanced feeding of preserved colostrum in neonatal cross-bred calves on the health status, growth, haematological, biochemical and hormonal parameters and to find any correlations exist among these factors during their first month of life. Fresh colostrum was collected in hygienic conditions from recently calved healthy cows from the first six milkings and then pooled. The pooled colostrum was preserved in dry sterile bottles by deep freezing at -20°C until fed to calves. Crude protein content of colostrum and whole milk were estimated. Total. viable count of pooled colostrum samples were recorded before and after ultra violet irradiation for 30 minutes. Twelve numbers of healthy neonatal crossbred calves of either sex of the Kerala Agricultural University Livestock Farm, College of Veterinary and Animal Sciences, Mannuthy were divided into two groups as Group I (control) and Group II (experimental) with six calves in each group. The calves of group I were fed with colostrum for three days and then milk (one-tenth of body weight) as